Trophic cascades in bell miner‐associated dieback forests: Quantifying relationships between leaf quality, psyllids and Psyllaephagus parasitoids. (12th July 2014) - Steinbauer, Martin J.; Sinai, Katherine M. J.; Anderson, Annette; Taylor, Gary S.; Horton, Bryony M.
Abstract Coteries of the meliphagid bird Manorina melanophrys are associated with a form of eucalypt defoliation and recovery called bell miner‐associated dieback (BMAD). Through their defence of cooperative colony boundaries against other insectivorous birds, bell miners may foster greater abundances of lerp‐forming psyllids (Hemiptera: Aphalaridae), some of which reduce the lifespan of leaves. Trophic cascades in BMAD forests need to be understood to have a complete picture of regulatory processes. We studied relationships between leaf quality, psyllid and Psyllaephagus parasitoid/hyperparasitoid abundances within the Gondwana Rainforest World Heritage Area, NSW, Australia; our focal tree species were Eucalyptus propinqua and E. biturbinata. Eucalyptus biturbinata had tougher leaves than E. propinqua; leaf toughness of both species varied with site and tree. We found a statistically significant, negative relationship between toughness (surrogate for leaf age) and foliar nitrogen content; younger leaves had higher nitrogen contents. Both bell miner abundance and foliar nitrogen were positively correlated with psyllid abundance. The abundance of Glycaspis species (the psyllid that produces lerps with the highest sugar content) was more closely correlated with foliar nitrogen content than was the abundance of all five psyllid genera combined. We identified 14 Psyllaephagus spp./morphospecies, comprising 11 primary parasitoids and three hyperparasitoids. The abundance of all Psyllaephagus combined was positively correlated with the abundance of lerps. However, psyllid parasitism was not correlated with the abundance of lerps. The abundance of the three hyperparasitoids was positively correlated with the abundance of Psyllaephagus hosts. The availability of epicormic foliage (young, morphologically juvenile leaves produced following defoliation) is likely to alter the nutritional ecology underpinning the diversity and abundance of psyllid populations. Higher quality epicormic foliage should favour populations of Glycaspis species (by enhancing nymphal survival) creating lerp hotspots that induce residency by opportunistic bell miners. The positive contribution of induced amelioration, interacting with feedbacks from parasitoids and hyperparasitoids, to BMAD requires longitudinal investigation.